2015
DOI: 10.1186/s12970-015-0088-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a moderate intake of beer on markers of hydration after exercise in the heat: a crossover study

Abstract: BackgroundExercise in the heat causes important water and electrolytes losses through perspiration. Optimal rehydration is crucial to facilitate the recuperation process after exercise. The aim of our study was to examine whether a moderate beer intake as part of the rehydration has any negative effect protocol after a short but dehydrating bout of exercise in the heat.MethodsSixteen active male (VO2max, 56 ± 4 mL/kg/min), were included in a crossover study and performed a dehydrating exercise (≤1 h running, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 27 publications
3
28
0
1
Order By: Relevance
“…In contrast to the large amounts of alcohol (ranging from 50–120 g alcohol) that was used in aforementioned studies, the present study aimed to reflect the normal-life situation of older adults and therefore used a more moderate amount of 30 g of alcohol. Recent research supports our finding that moderate amounts of full-strength beer (≥4.5%, 20–40 g alcohol) does not affect hydration in dehydrated [ 20 , 21 ] and euhydrated (young) men [ 14 ].…”
Section: Discussionsupporting
confidence: 85%
“…In contrast to the large amounts of alcohol (ranging from 50–120 g alcohol) that was used in aforementioned studies, the present study aimed to reflect the normal-life situation of older adults and therefore used a more moderate amount of 30 g of alcohol. Recent research supports our finding that moderate amounts of full-strength beer (≥4.5%, 20–40 g alcohol) does not affect hydration in dehydrated [ 20 , 21 ] and euhydrated (young) men [ 14 ].…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, it has been suggested that a moderate consumption of regular beer could be accepted in a healthy diet because moderate drinking may have some health benefits. For instance, a crossover study showed that moderate consumption of beer facilitates the recovery of the hormonal and immunological metabolism in active individuals after physical exercise [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that the subjects along the ad libitum properly replaced the fluids up to -2% loss of body mass. 21 According to Jiménez-Pavón et al 20 found that any parameter measured was not negatively affected by the consumption of beer. The water balance and urine excretion values were not different between the tactics of rehydration.…”
Section: Base -Bielefeld Academic Search Enginementioning
confidence: 98%